Association between smoking and non-alcoholic fatty liver disease in Southeast Asia - Mumtaz, Hassan; Hameed, Madiha; Sangah, Abdul Basit; Zubair, Amraha; Hasan, Mohammad (Frontiers in Public Health, 2022)
An estimated 8 million people die each year from tobacco smoking, with an increasing frequency recently being observed in Southeast Asian countries, which is a preventable risk factor for mortality. NAFLD, fibrosis, advancement of hepatocellular carcinoma, and prognosis for those with severe liver disease are all negatively influenced. NAFLD and cigarette usage seem to be a direct link. Oxidative stress and oncogenic signals have been implicated in cancer development in animal models and human clinical trials. The elevated risk of cardiovascular disease and malignancies in those with steatohepatitis and those who have had liver transplants is exacerbated by smoking. We found that smoking cessation may increase treatment response and fibrosis regression rates, decrease hepatocellular carcinoma incidence, and improve liver transplant outcomes. In the last segment, we'll look at electronic cigarettes, a hot subject in public health right now, as well as additional repercussions of smoking.